A Clinical Dilemma Of Bilateral Hematosalpinx In Ectopic Pregnancy: Case Report - Ratu Astuti Dwi Putri; Fadler Hidayat; Donel Suhaimi; Tubagus Odih Rhomdaniwahid (Medica Hospitalia : Journal of Clinical Medicine, 2024)
Background: Blastocyst implantation outside the uterine cavity leads to ectopic pregnancy. About 96% of ectopic pregnancies occur in the fallopian tubes, where it most frequently occurs; the fimbrial end accounts for 11% of all ectopic pregnancies. There was an uncommon type of ectopic pregnancy called bilateral tubal ectopic pregnancy. Bilateral tubal ectopic pregnancy is estimated to affect 1 out of 725 - 1580 ectopic pregnancies or 1 out of 200,000 live births. However, the villi quickly penetrate the endosalpinx once the implantation of the ectopic pregnancy has occurred before reaching the tubal wall and peritoneum. Vascular growth and a peritubal hematoma or hematosalpinx, which frequently involves the contralateral tubal section, are also present with this penetration. The purpose of this article is to report on the dilemmas that often occur in the case of bilateral hematosalpinx in ectopic pregnancy. Case Description: In this report, we discuss a 33-year-old woman with a positive pregnancy test and transvaginal ultrasound result that was suggestive of ectopic pregnancy in a stable hemodynamic state. The patient underwent an exploratory laparotomy, which showed bilateral hematosalpinx with right ectopic pregnancy with damaged fimbria. The left fallopian tube had a blue-purple bulge that suggested hematosalpinx secondary to ectopic pregnancy rather than bilateral ectopic pregnancy condition. The decision for deﬁnitive management was made, right salpingectomy puncture and drainage of the hematosalpinx were performed without complication. The ﬁnal diagnosis was conﬁrmed on pathology examination that showing chorionic villi within the right damaged fimbria, focal decidua, a few trophoblast-like cells that indicated ectopic pregnancy in the left tubal cavity. Conclusion: This approach encourages both shared decision-making and preparedness, both of which are required to provide patient-centered and comprehensive caremanagement such as bilateral hematosalpinx in ectopic pregnancy case, that must always be individualized, and patient's desire for future conception must be taken into account.